Brain angiotensin-(1–7)/Mas axis: A new target to reduce the cardiovascular risk to emotional stress. (April 2016) - Fontes, Marco Antônio Peliky; Martins Lima, Augusto; Santos, Robson Augusto Souza dos
Abstract: Emotional stress is now considered a risk factor for several diseases including cardiac arrhythmias and hypertension. It is well known that the activation of neuroendocrine and autonomic mechanisms features the response to emotional stress. However, its link to cardiovascular diseases and the regulatory mechanisms involved remain to be further comprehended. The renin–angiotensin system (RAS) plays an important role in homeostasis on all body systems. Specifically in the brain, the RAS regulates a number of physiological aspects. Recent data indicate that the activation of angiotensin-converting enzyme/angiotensin II/AT1 receptor axis facilitates the emotional stress responses. On the other hand, growing evidence indicates that its counterregulatory axis, the angiotensin-converting enzyme 2 (ACE2)/(Ang)iotensin-(1–7)/Mas axis, reduces anxiety and attenuates the physiological responses to emotional stress. The present review focuses on angiotensin-(1–7)/Mas axis as a promising target to attenuate the physiological response to emotional stress reducing the risk of cardiovascular diseases. Highlights: Emotional stress is considered a risk factor to several diseases. Neuroendocrine and autonomic mechanisms feature the response to emotional stress. Activation of ACE Ang II/AT1 receptor axis enhances responses to emotional stress. Activation of ACE2/Ang-(1–7)/Mas axis attenuates responses to emotional stress. Ang-(1–7)/Mas axis is a promising target to reduce the risk of stress-related diseases.